Teachers’ perspectives on the factors influencing organisational resilience: a qualitative study - Yıldızoğlu, Hüseyin; Topcu, Zuhal (Technium Social Sciences Journal, 2025)
This study aims to reveal the factors that positively or negatively affect the organizational resilience of educational institutions from the perspective of teachers. A phenomenological design, one of the qualitative research methods, was adopted in the study, and a semi-structured interview technique was used to collect data. The participant group consisted of 20 teachers working at different levels of education in public schools. These teachers were selected using maximum variation sampling, a purposive sampling method, and included 5 preschool, 5 primary school, 5 middle school, and 5 high school teachers. According to the teachers' opinions, the factors that positively affect the organizational resilience of educational institutions were grouped under four main themes: "collaboration and institutional culture," "crisis and change management," "leadership competencies," and "supportive resources and infrastructure." Participants stated that solidarity and cooperation among employees, acting in unity and solidarity, organisational culture, developing applicable crisis plans, generating rapid solutions to crises, adapting quickly to change, leadership, and technological infrastructure competence contribute to the successful management of educational institutions in crisis situations. Factors that negatively impact the organizational resilience of educational institutions are categorized under four themes: "management and communication problems," "resistance to change and lack of motivation," "infrastructure deficiencies," and "unpreparedness and uncertainty." According to teachers, the primary factors negatively impacting organizational resilience include lack of planning, lack of functional and applicable crisis plans, inadequate technological infrastructure, a lack of openness to innovation and change, low motivation, and a lack of foresight. The findings provide guidance for school administrators and policymakers in developing strategies that will make educational institutions more resilient to crises. This will enable educational institutions to not only overcome crises but also emerge stronger from these processes.